Processing and characterization of proton conducting material based on cerate-zirconate ceramics - Nafisah Osman,; Nur Syafkeena Mohd Affandi,; Oskar Hasdinor Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Solid electrolyte based on cerate-zirconates have been widely investigated world-wide as proton conductor for potential applications in electrochemical devices such as fuel cells, electrochemical sensors, reactors, and devices. The most conventional physical method to prepare these ceramic electrolytes is via solid-state reaction (SSR). However, chemical method or known as wet chemical method (WCM) such as a sol-gel process has become a reliable route in terms of producing high purity and homogenous ultrafine powders. Tailoring the microstructure of the ceramics electrolyte can be achieved as sol gel process produces single perovskite phase of cerate-zirconates at lower processing temperature. This lower heat treatment produces the ceramics with improved quality for instance ultra-fine and agglomerate free powders with narrow size distributions. Subsequently, the innovative procedures generates high relative density of the electrolyte with improved quality and performance. Within the scope, in this paper we summarize our recent results on the synthesis of doped Ba(Ce,Zr)O3 nanopowders by a modified sol-gel routes using metal nitrate salts as precursor.